Analisa Pengendalian Kualitas pada Proses Azodicarbonamide dengan Pendekatan Metode Six Sigma - Syahriyanti, Rizki; Rosihin, Rosihin; Dwiputra, Gerry Anugrah (Universitas Serang Raya, 2018)
Foaming Agent company is a company engaged in the chemical industrial manufacturing, especially the additive industry for plastic and synthetic rubber. In the production process, the Foaming Agent Company has a problem with one of its products, Azodicarbonamide (ADCA). The number of defects caused becomes a problem primarily related to the course of production and the relationship with the customer. The research was conducted using the Six Sigma method by implementing DMAIC (Define, Measure, Analyze, Improve, Control). This study aims to identify the factors that cause defects and the most optimal choice of options to increase the level of sigma in the ADCA production process. Based on the results the most significant aspects that cause defects in ADCA products is Average Particle Size; 66.77% of the overall production defects. The sigma level that obtained before and after the improvisation is 3.68 and 4.03 with the average achieved savings per month are Rp.600 million. The results of the gradual decrease in defects showed that the options implemented at the improvisation stage were successful, but still needed improvisation so that the companys performance can be even better